Exploring Successful Small Urban Spaces" Criteria with Emphasis on Cultural Context - Partovi, Parvin (Array, 2021)
In the crowded cities of the present age, public spaces can provide a quiet area away from the hustle and bustle of the city that citizens can interact with by incorporating utility features and meeting human needs and Relax there. Small urban spaces are among the most important and effective urban spaces to achieve this goal. Because these spaces due to their small size and lower costs (compared to larger spaces) for construction can be created in large numbers and distributed throughout the city. In this way, citizens will be able to reach a public urban space on foot in a short time. If these spaces are well designed, they can encourage people to stay in and interact with each other. It is not difficult to identify and experience high-quality successful places, but identifying the reasons for their success is difficult and even more difficult, understanding if similar spaces in other places can be considered successful. This question is important because public space with deep social content is considered a cultural product. Public space is the product of the historical and socio-cultural forces of society. Therefore, one of the most important issues that should be considered in the study of public spaces and the reasons for their success is the cultural context. In Iranian cities that have been influenced by the values and principles of Islam,recognizing Islamic principles and their role in shaping public spaces can lead us to desirable results. The purpose of this article is to develop a conceptual model of successful small urban spaces with an emphasis on cultural issues, especially in Iranian-Islamic cities. In this regard, the effective criteria for the success of urban spaces in general and small urban spaces in particular in the two categories of Western countries and Iranian Islamic cities were examined and then, taking into account the criteria derived from cultural theorists, the conceptual model of research with 38 subcriteria is provided.